2004
DOI: 10.1002/ejic.200400124
|View full text |Cite
|
Sign up to set email alerts
|

Structure Comparison of Early and Late Lanthanide(III) Homodinuclear Macrocyclic Complexes with the Polyamine Polycarboxylic Ligand H8OHEC

Abstract: The solid‐state structures of two new homodinuclear chelate complexes with the late lanthanide(III) ions Yb and Lu, [Na2(Yb2OHEC)].14.5H2O (1), and [Na2(Lu2OHEC)].14.5H2O (2) (H8OHEC = 1,4,7,10,14,17,20,23‐octaazacyclohexacosane‐ 1,4,7,10,14,17,20,23‐octaacetic acid), have been determined by X‐ray crystal structure analysis. Each lanthanide(III) ion is coordinated by eight donor atoms of the ligand and the geometry of the coordination polyhedron approaches a bicapped trigonal prism. These structures are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Hovland and coIn the last decades, nuclear magnetic resonance imaging has evolved as a powerful tool for research and practice in workers prepared a novel Gd(III)-87 complex, which showed high T 1 -relaxivity values in serum albumin solutions, blood and plasma [99]. membered ring formed from the eight amine and bridging ethylene or propylene groups, was synthesized and its properties as a chelator for lanthanides and small transition metals also was studied [100][101][102][103]. For increasing the rotational correlation time compared with conventional DOTA and DTPA and obtaining previously unknown binuclear contrast agents with two closely sited gadolinium ions, H 8 OHEC (1,4,7,10,14,17,20,23-octaazacyclohexacosane-1,4,7,10,14,17,20,23-octaacetic acid) (88), which is a macrocyclic polyaminocarboxylate with a 26-atom-…”
Section: Contrast Agents For Magnetic Resonance Imagingmentioning
confidence: 99%
“…Hovland and coIn the last decades, nuclear magnetic resonance imaging has evolved as a powerful tool for research and practice in workers prepared a novel Gd(III)-87 complex, which showed high T 1 -relaxivity values in serum albumin solutions, blood and plasma [99]. membered ring formed from the eight amine and bridging ethylene or propylene groups, was synthesized and its properties as a chelator for lanthanides and small transition metals also was studied [100][101][102][103]. For increasing the rotational correlation time compared with conventional DOTA and DTPA and obtaining previously unknown binuclear contrast agents with two closely sited gadolinium ions, H 8 OHEC (1,4,7,10,14,17,20,23-octaazacyclohexacosane-1,4,7,10,14,17,20,23-octaacetic acid) (88), which is a macrocyclic polyaminocarboxylate with a 26-atom-…”
Section: Contrast Agents For Magnetic Resonance Imagingmentioning
confidence: 99%